Evaluation the Effects of Dietary Cholecalciferol Substitution with 1alpha-Hydroxycholecalciferol on Performance and Tibia Parameters in Broiler Chickens - Landy , N.; Toghyani, M. (International Journal of Poultry Science, 2014)
This experiment in broiler chickens was conducted to test the efficacy of feeding 1alpha-OH D3 as a replacement for cholecalciferol on performance, tibia quality and severity of tibial dyschondroplasia (TD). On the day of hatch 96 as hatched broiler chickens (Ross-308) were weighted and randomly allocated to two treatment groups, each with 4 replicate pens of 12 chicks. The dietary treatments were as follows: basal diet+5μg/kg of 1alpha-OHD3, or basal diet+5000 IU/kg vitamin D3. The broiler house was completely enclosed and lighting was provided by incandescent bulbs. No significant differences (p>0.05) were observed on daily feed intake, body weight and feed conversion ratio whereas it tended to improve in broilers fed basal diet supplemented with 5μg/kg of 1alpha-OHD3 diet (p>0.05). No significant differences (p>0.05) were found between broilers fed basal diet plus 1alpha-OHD3 or the same basal diet plus cholecalciferol for any of tibia variables measured, whereas it tended to increase in broilers fed basal diet supplemented with 5μ g/kg of 1alpha-OHD3 (p>0.05). Treatments failed to induce any effect on TD scores at d 42, though it tended to increase in broilers fed diets containing 5μg/kg of 1alpha-OHD3 (p>0.05). In conclusion, the results indicate that supplementing 1alpha-OHD3 as a replacement for cholecalciferol could promote performance and tibia parameter and it increased severity of TD, whereas the results were not statistically significant.